2007
DOI: 10.1111/j.1365-2702.2007.01600.x
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and the information needs and dilemmas of first‐time mothers over 35 years

Abstract: As the number of childbearing women over 35 years continues to grow, it is important for health professionals to understand the particular needs of this group. In doing so, doctors, midwives and maternal and child health nurses may be in a position to provide more meaningful maternal support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
112
2
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(131 citation statements)
references
References 41 publications
(42 reference statements)
6
112
2
11
Order By: Relevance
“…However, they often felt that women had difficulties to remember all the information. This is in line with other studies reporting an information overload among pregnant women [15,36]. Similarly, a pilot test of an app to monitor gestational weight gain found that it could help pregnant women to cope with the great amount of information provided by different sources [37].…”
Section: Discussion Principal Resultssupporting
confidence: 76%
“…However, they often felt that women had difficulties to remember all the information. This is in line with other studies reporting an information overload among pregnant women [15,36]. Similarly, a pilot test of an app to monitor gestational weight gain found that it could help pregnant women to cope with the great amount of information provided by different sources [37].…”
Section: Discussion Principal Resultssupporting
confidence: 76%
“…22,23 Our finding suggests the possibility of early identification and intervention starting at birth, a time when parents may be most receptive to health information. 24,25 Strategies might include anticipatory guidance through postpartum home visits by a public health nurse, instead of waiting for the infant's first encounter with the medical system or until the first immunization is missed. Another strategy is to engage the midwife to promote immunization, as women choosing a midwife delivery continue to receive midwifery care until 6 weeks after delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Carolan (2007) argues that there is a growing trend for well-educated and well-resourced individuals to request additional healthcare information from health professionals and for it to be provided, -T reflected in health visitor comments in particular. Issues of reliability were also raised, one of the projec intain a supportive atmosphere whilst ensuring mothers did not share ; and the health visitor attempting to (unsuccessfully) direct mothers to underutilised library resources.…”
Section: Information Overload and Unmet Needsmentioning
confidence: 99%